(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Blockchain technology has a wide range of applications, including supply chain management (SCM), where it may replace mid-size activities in many transaction-based processes throughout the supply chain. Blockchain technology has a disruptive effect on the growth and operation of the supply chain, making it extremely essential to investigate future possibilities for usage. Supervision and monitoring are becoming very complex as proper utilization become increasingly globalized. Blockchain platform, as a decentralized digitized advanced technologies that assures accountability, authenticity, and privacy, has the capacity to solve various global supply chain administration concerns. Distributed supply chain coordination, material and data flow coordination, virtual companies, agile supply chain management, supply chain management flexibility, supply chain measurement, supply chain resilience, risk and reel effect, real-time controls, and supply chain-based service are all technical potential problems associated with blockchain advancement discussed in this study. This research looks at a variety of sectors, including shipping, manufacturing, and automotive, aviation, finance, technology, energy, health, food and farming, e-commerce, and education, to see how blockchain technology may help with visibility and business process management. In addition to future theoretical studies, technical and engineering research is critical for a variety of supply chain issues.